The bench press: A comparison between flat-back and arched-back techniques - Tungate, P. (Strength and Conditioning Journal, 2019)
The arch-back bench press technique is becoming more common with the rising popularity of the sport of powerlifting. This technique is best implemented by coaches who aim for their advanced athletes to handle higher loads with reduced range of motion in mesocycles where strength and power are prioritized. Other methods are available for nonpowerlifting athletes to obtain the same results without learning this technique.